PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN USAHATANI SAYUR DARI KELOMPOKTANI BARU TERBIT DI KELURAHAN OENESU KECAMATAN KUPANG BARAT - Ardianus Verdi; Serman Nikolaus; Alfetri N. P. Lango (Undana Press, 2021)
Astudy had been carried at the Village of Oenesu, the SubDistrict of West Kupang, the District of Kupang, since August until November 2020. The main objective of this study was to understand the roles of field agricultural workers in developing the vegetable farming operated by farmers grouping in the Nascent Farmer Group located at the Village of Oenesu, the Sub District of West Kupang, the District of Kupang. The study was applied a survey method. Research location was determine purposively based on a consideration that in this location was never conducting a study like this. Population of this study were farmers, both managers and members, operating the vegetable farming in the Nascent Famer Group. Totally they were 25 persons in number, consisted of managers were 3 persons, and members were 22 persons. Because the number of population were too small, then they were all been as the sample of study. So the size of sample used in this study was 25 farmers determined sensusly. Moreover, the primary data collected by face to face interview with respondent, for quantitative data were analyzed by the use of mean score, frequencies, and percentage, meanwhile for the qualitative data were described appropriate with their points. Result of data analysis indicated that the role of field agricultural extension worker in developing the vegetable farming was in “good enough category”,where the percentage value of mean score in achieving the maksimums core was 58%.